A Novel Diagnostic Method to Detect Duck Tembusu Virus: A Colloidal Gold-Based Immunochromatographic Assay - Yu, Guanliu; Yu, Xianglong; Yang, Guoping; Tang, Yi; Diao, Youxiang (Frontiers in Microbiology, 2018)
Duck Tembusu virus (DTMUV) is an emerging pathogenic flavivirus that has resulted in large economic losses to the duck-rearing industry in China since 2010. Therefore, an effective diagnostic approach to monitor the spread of DTMUV is necessary. Here, a novel diagnostic immunochromatographic strip (ICS) assay was developed to detect DTMUV. The assay was carried out using colloidal gold coated with purified monoclonal antibody A12D3 against envelope E protein. Purified polyclonal C12D1 antibodies from BALB/c mice against the envelope E protein were used as the capture antibody. Goat anti-mouse IgG was used to detect DTMUV, which was also assembled on the ICS. Results showed that the ICS could specifically detect DTMUV within 10 min. It also could be stored 25°C and 4°C for 4 and 6 months, respectively. The sensitivity of the ICS indicated that the dilution multiples of positive allantoic fluid of DTMUV (LD50: 104.33/0.2 ml) was up to 200. Its specificity and sensibility showed no significant change under the above storage situations. 50 clinical samples were simultaneously detected by ICS and reverse-transcription polymerase chain reaction with a 93.9% coincidence rate between them. It proved that the ICS in present study was highly specific, sensitive, repeatable, and more convenient to rapidly detect DTMUV in clinical samples.